The Effects to Trend the Suitable OS Platform - Aladdin, Aso Mohammed; Bakir, Yad N.; Saeed, Sarwar I. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2018)
Technically, software is a part of electronic devices that is responsible for managing hardware. The signaling communication between hardware and software ultimately controls electronic devices, and is known as Operating System (OS). For the purpose of selecting the best platform for clients, users should study functionalities, securities, graphic interfaces and usability of the different OS platforms. Therefore, this research focuses on choosing the suitable OS platform for user in academic and non-academic environments, according to demanding users’ companionability. It also explains the first type of OS which can be utilized openly. In addition to that, it concentrates on some general significant aspects that are useful for OS users.